2020
DOI: 10.1007/s40843-020-1446-5
|View full text |Cite
|
Sign up to set email alerts
|

Sponge-templating synthesis of sandwich-like reduced graphene oxide nanoplates with confined gold nanoparticles and their enhanced stability for solar evaporation

Abstract: Solar evaporation based on plasmonic metal nanoparticles (MNPs) is emerging as a promising technology. However, the fine structure of MNPs is unstable, and both the high temperature generated by intensive light and corrosive ions in water could damage them. The performance will decline after recycling and long-time usage. To address these issues, we adopted a sponge-templating method for preparing sandwich-like nanoplates with the gold nanoparticles (Au NPs) confined in reduced graphene oxide (rGO) nanosheets.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…As a pivotal component of ISSG system, solar absorber acts as photo-thermal converter to provide thermal energy for water evaporation [10,11]. Until now, various types of solar absorbers have been developed, including metal nanoparticles [12][13][14][15][16], semi-conductor material [17], conjugated polymer [18], carbon material [19][20][21][22][23], and hydrogel [24,25]. Despite the significant progress achieved, these absorbers usually show drawbacks of high cost and complex synthesis process.…”
Section: Introductionmentioning
confidence: 99%
“…As a pivotal component of ISSG system, solar absorber acts as photo-thermal converter to provide thermal energy for water evaporation [10,11]. Until now, various types of solar absorbers have been developed, including metal nanoparticles [12][13][14][15][16], semi-conductor material [17], conjugated polymer [18], carbon material [19][20][21][22][23], and hydrogel [24,25]. Despite the significant progress achieved, these absorbers usually show drawbacks of high cost and complex synthesis process.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, inherent bioactive molecules, which are easily used as capping and stabilizing agents are major factors that participate in the steady rise of this method adoption. Several studies reported the use of living materials such as plants, bacteria, algae, fungi, and sponge extract for the green synthesis of nanoparticles [19][20][21][22]. In light of the above mentioned useful properties and the ever increasing probability of exposure to monometallic and bimetallic nanoparticles, it is vital to develop an environmental friendly, sustainable synthetic, and cost effective approach for the fabrication of metallic nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…This mixture was then further coated with rGO producing rGO/Au/rGO nanoplates and added on a hydrophilic substrate base as water transport. The wrinkled nanoplates with a broad light absorption of 400–1200 nm resulted in a maximum 75.5 °C surface temperature and a water evaporation rate of ∼1.15 kg m −2 h −1 with 63.35 % efficiency under 1 sun [10b] …”
Section: Solar Absorber Selectionmentioning
confidence: 99%